2019
DOI: 10.1037/ppm0000169
|View full text |Cite
|
Sign up to set email alerts
|

My friend Harry’s a wizard: Predicting parasocial interaction with characters from fiction.

Abstract: We explored parasocial interactions with characters from a narrow range of books and movies, namely those featuring the character 'Harry Potter'. Following research which suggests that parasocial interactions are multidimensional, we investigated which personality, reading and viewing motives, predicted four dimensions of parasocial interaction with characters in the 'Harry Potter' series. The pattern of significant predictors indicated that interpersonal aspects of reading (neuroticism, reading for companions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Much of the initial research on PSRs focused on one-sided relationships with real, as opposed to fictional, personalities, for example, news readers (Levy, 1979). Latterly researchers have also examined PSRs with characters such as those from soap operas (Perse & Rubin, 1989) and popular books and movies (Ingram & Luckett, 2019). Differing types of PSRs have been highlighted by Giles (2002), who noted that PSRs with personalities who directly address the audience are “first-order,” whereas those with fictional characters are “second-order.” It may be expected that PSRs are stronger for personalities whom an individual can actually meet.…”
Section: Parasocial Relationshipsmentioning
confidence: 99%
See 3 more Smart Citations
“…Much of the initial research on PSRs focused on one-sided relationships with real, as opposed to fictional, personalities, for example, news readers (Levy, 1979). Latterly researchers have also examined PSRs with characters such as those from soap operas (Perse & Rubin, 1989) and popular books and movies (Ingram & Luckett, 2019). Differing types of PSRs have been highlighted by Giles (2002), who noted that PSRs with personalities who directly address the audience are “first-order,” whereas those with fictional characters are “second-order.” It may be expected that PSRs are stronger for personalities whom an individual can actually meet.…”
Section: Parasocial Relationshipsmentioning
confidence: 99%
“…Differing types of PSRs have been highlighted by Giles (2002), who noted that PSRs with personalities who directly address the audience are “first-order,” whereas those with fictional characters are “second-order.” It may be expected that PSRs are stronger for personalities whom an individual can actually meet. However, it has been suggested that PSRs, as a predictor of enjoyment, were stronger for fictional programming (Nabi, Stitt, Halford, & Finnerty, 2006), and that, for individuals with specific engagement motives, PSRs can be manifested in a desire to meet a fictional character (Ingram & Luckett, 2019). Although, critically, when PSRs are based on live action TV or movies, it may be difficult for viewers to discern the character from the actor.…”
Section: Parasocial Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the depth of these relationships may be measured on a dimension of intimacy, as indicated when the reader agrees with scale items such as "I have an intimate connection with my favorite character," or "I see my favorite character as a close friend." Ingram and Luckett (2019) studied parasocial relationships arising from the Harry Potter series of books and movies and found that certain personality characteristics were likely to be associated with higher scores on these dimensions for avid readers of the series; specifically, the personality trait of agreeableness predicted intimacy and familiarity among readers: Participants high in agreeableness, as measured with a Big Five inventory, were more likely to seek intimacy with their favorite character from the Harry Potter books and to report having a high degree of familiarity with him or her (or it). The relatively strong association of the personality trait of agreeableness and empathy has been well established (Graziano et al, 2007;John & Srivastava, 1999;Penner et al, 1995).…”
Section: Social Cognitive Learningmentioning
confidence: 99%